Capital structure as an element of the corporate governance system in Ukraine - Alexander Kostyuk (Journal for East European Management Studies, 2003)
The paper considers the problems of corporate governance in Ukraine during the process of transformation of the structure of corporate ownership. Capital structure, as an element of the system of corporate governance, is investigated. A tight connection between concentration of shareholders equity, equity cost and capital structure (financial leverage) has been found as a result of research. The higher the concentration of shareholders equity, the larger the share of debt in the capital structure and the higher the cost of equity. Thus, the capital structure of Ukrainian companies is an efficient indicator of corporate governance performance. – – Der Aufsatz befasst sich mit den Problemen der Unternehmensorganisation im Transformationsprozess der Unternehmensbesitzstrukturen. Die Struktur des Kapitals als Element des Systems wird untersucht. Eine enge Verbindung zwischen der Konzentration von Kapital der Anteilseigner, Kapitalkosten und Kapitalstruktur (dem Verhältnis von Fremd- zu Eigenkapital) kristallisierte sich als Ergebnis der Untersuchung heraus. Je höher die Konzentration von Kapital der Anteilseigner, desto grösser der Anteil an Schulden in der Kapitalstruktur und somit entstehen auch höhere Kapitalkosten. Somit stellt die Kapitalstruktur von ukrainischen Unternehmen einen effizienten Indikator für die Leistung von Unternehmensorganisation dar.
Keywords: 650; Capital structure; credit markets; corporate ownership structure; cost of capital; Ukraine